Bucking Conservatism Alternative Stories of Alberta from the 1960s and 1970s - Crane Bear, Leon; Hannant, Larry; Patton, Karissa Robyn (Athabasca University Press, 2021)
With lively, informative contributions by both scholars and activists, Bucking Conservatism highlights the individuals and groups who challenged Alberta's conservative status quo in the 1960s and 70s. Drawing on archival records, newspaper articles, police reports, and interviews, the contributors examine Alberta's history through the eyes of Indigenous activists protesting discriminatory legislation and unfulfilled treaty obligations, women and lesbian and gay persons standing up to the heteropatriarchy, student activists seeking to forge a new democracy, and anti-capitalist environmentalists demanding social change. This book uncovers the lasting influence of Alberta's noncomformists---those who recognized the need for dissent in a province defined by wealth and right-wing politics---and poses thought-provoking questions for contemporary activists.